An Analysis of Queen Elizabeth II’s Coronavirus Speech Using Hyland’s Metadiscourse Theory - BALOG, PERSIEUS (International Journal of Arts, Sciences and Education, 2022)
Queen Elizabeth II delivered a special speech to Britain and the Commonwealth of Nations on April 5, 2020. This special broadcast is considered to be the fifth of its kind to be delivered by Her Majesty The Queen. This speech was delivered when the world was facing global pandemic and when British Prime Minister Boris Johnson was infected by the coronavirus, thus making its rhetorical situation or context unique. In this regard, some scholars have been interested in analyzing this type of rhetoric. Drawing from Hyland’s Metadiscourse Theory, the present study aims to analyze how Queen Elizabeth II conveys information and content and interacts to listeners using metadiscourse markers. Findings reveal that Queen Elizabeth II used more interactional metadiscourse markers than interactive metadiscourse markers in her coronavirus speech. It indicates that the queen values involving her audiences in the speech and building relationship with them. Moreover, results show that pragmatic meanings of words should be considered in analyzing metadiscourse markers. Additionally, based on the analysis of interactional resources, it shows that Queen Elizabeth II used engagement markers and self-mentions in different ways such as showing that they are united as one country, expressing support, appreciation, and gratitude to the front liners, and sharing personal story to connect the past to the present. Overall, findings reveal that Queen Elizabeth II used interactional and interactive resources to build relationship with people and guide them in her speech to clearly understand her message.